Answer:
a,d
Step-by-step explanation:
Answer: 4. (-1,-1) 3. (3,-2)
4)
Set the equations equal to each other.
4x+3=-x-2
Subtract 3 from both sides
4x=-x-5
Add x to both sides
5x=-5
Divide both sides by 5
x=-1
Next, replace x with -1 in either equation to find y.
-(-1)-2=y
-1=y
3)
Do the same thing for this one and set them equal to each other
-2x+4=-1/3x-1
Add 1 to both sides
-2x+5=-1/3x
Add 2x to both sides
5=5/3x
Divide both sides by 5/3
x=3
Next, replace x with 3 in either equation
-2(3)+4=y
-2=y
Step-by-step explanation:
i hope this will help you
Answer:
answer is b
Step-by-step explanation:
hope it helps!!!